Tuberculosis score chart signs and symptoms in children with positive tuberculin skin tests - Finny Fitry Yani; Rizanda Machmoed; Marhefdison Marhefdison; Darfioes Basir (Indonesian Pediatric Society Publishing House, 2012)
Background The Indonesian Pediatrics Respirology Working Group (IPRWG) developed the tuberculosis (TB) score chart to assist in diagnosing TB in community health centers (Puskesmas). Objectives To document signs and symptoms of the IPRWG TB score chart, to analyze various combinations of these signs and symptoms, and to compare these combinations in children with TB to those without TB, based on a TB score chart. Methods We performed a cross-sectional study from July to October 2008, in Padang, Bukittinggi and Pasaman. We recruited children with known positive tuberculin skin tests (TST) from a 2006 tuberculin survey. Questionnaires on signs and symptoms (IPRWG TB score chart) were completed and chest radiographs were obtained for all children. Subjects fulfilling a total score of six or more were considered to have a diagnosis of TB. Results We diagnosed TB in 78/285 (27.3%) subjects. A score value of3 for the category of household contact (HHC) positive smears was added in 21/78 subjects. However, the highest risk for TB disease was found in those diagnosed with no clear history of HHC (58.9%; OR 192, 95% CI 22 to 1679). The highest risk factors for TB were suggestive chest X-ray (34.6%; OR 9.2, 95% CI 3.6 to 23 .4) and fever lasting > 2 weeks (17.9%; OR 8, 95% CI 2.2 to 29.1), respectively. Of 46 children with TB diagnosis but without HHC, the combination of undernourishment, lymph node enlargement and suggestive chest X-ray was highest (28.2%). Individual or dual combination signs and symptoms were also found in children without TB diagnosis. Conclusion Various combinations of signs and symptoms could lead to fulfillment of scoring for TB diagnosis. [Paediatr lndones. 2012;5 2: 78-85].